CHILD COMPREHENSION OF ADULTSâ€™ VERBAL INPUT: A CASE OF BILINGUAL ACQUISITION IN INFANCY - Adnyani, Ni Luh Putu Sri; Beratha, Ni Luh Sutjiati; Suparwa, I Nyoman (Indonesian Journal of Applied Linguistics, 2017)
Research concerning comprehension in early simultaneous bilingualism is still very limited. Thus, this study focuses on describing a bilingual infantâ€™s comprehension of adultsâ€™ verbal input addressed to the child in an Indonesian-German language environment, and the childâ€™s understanding of translation equivalents (TEs). The child, who was exposed to Indonesian and German simultaneously from birth, was observed from age 0;9 to age 1;3 using a diary supplemented with weekly video recordings. A â€œone parent-one languageâ€ system was applied in which the child received Indonesian language from the mother and German language from the father from birth. Since the family live in Indonesia and have regular contact to the collective family members, the child received dominant exposure in Indonesian compared to German. The data was transcribed and analysed using ELAN. The results show that the adultsâ€™ verbal inputs in the form of speech addressed to the child were in the form of short utterances which very often had a high-pitched sound and were rich in repetition. The adultsâ€™ speech was able to be discriminated by the child. In the pre-production stage, the child could understand approximately 6 (six) proper nouns, 18 (eighteen) Indonesian words and 14 (fourteen) German words. The result reveals that the child could comprehend more words in Indonesian than in German. It was also found that the child could understand some bilingual synonyms, which implies that at the pre-production stage, the child already went through a process of bilingual development.